PENGARUH BIAYA OPERASIONAL DAN PENJUALAN TERHADAP LABA BERSIH PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERCATAT DI BURSA EFEK INDONESIA TAHUN 2012-2018 - Saripah, Endah; Harahap, Muhammad Nasim (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2021)
ABSTRACK This study aims to determine the effect of operating costs and sales partially or simultaneously on net income. The problem that occurs in this study is the fluctuating net profit in various industrial sector manufacturing companies which are listed on the Indonesia Stock Exchange from 2012-2018. The method of analysis in this study uses multiple linear regression analysis with the help of SPSS 21 software. The results of the regression analysis test show that operating costs partially have a significant negative effect on net income, sales partially affect net income, while simultaneously operating costs and sales have a significant effect. against net income. To test the coefficient of determination or R2, the result is 0.346 or 34.6% of net income is influenced by these two variables. As for the remaining 65.4% which is influenced by other variables not examined in this study. Keywords: Operational Costs, Sales and Net Profits